Managing coopetition through horizontal supply chain relations: Linking dyadic and network levels of analysis - Wilhelm, Miriam M. (Journal of Operations Management, 2011)
AbstractA growing research stream has expanded the level of analysis beyond single buyer–supplier relations to the network, including supplier–supplier relations. These supplier–supplier relations may constitute a missing link between the traditional analysis of the dyadic and the network level of analysis that are often treated separately. This paper explores the interplay of the supplier–supplier and network of analysis by focusing on the inherent tension between cooperation and competition, using a multiple case study design in the Japanese and German automobile industries. It is argued that the buyer is able to exert influence not only on the coopetition level, so within “horizontal supply chain relations,” but that the coopetitive tension in the overall network can in fact be managedthroughthe active establishment and maintenance of such relations.